2009
DOI: 10.1111/j.1743-6109.2008.01117.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function and Tunica Albuginea Wound Healing Following Penile Fracture: An 18-year Follow-Up Study of 352 Patients from Kermanshah, Iran

Abstract: Introduction We present a study on the experiences of penile fracture in an Iranian population. Aim To determine the long-term outcome of penile fracture. Methods Between April 1990 and May 2008, 373 patients presented with clinical features suggestive of penile fracture. Of these, 11 declined surgery. The remaining 362 were operated upon using a degloving in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
118
1
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(135 citation statements)
references
References 14 publications
12
118
1
4
Order By: Relevance
“…11,13 Contemporary series showed that the incidence of ED after surgical repair of fracture penis ranges from 0% up to 16.6%. 6,7,[13][14][15][16][17][18][19] Several important issues may be raised during discussing the development of ED after surgical repair of fracture penis. First, is delayed presentation after trauma a risk factor for ED?…”
Section: Introductionmentioning
confidence: 99%
“…11,13 Contemporary series showed that the incidence of ED after surgical repair of fracture penis ranges from 0% up to 16.6%. 6,7,[13][14][15][16][17][18][19] Several important issues may be raised during discussing the development of ED after surgical repair of fracture penis. First, is delayed presentation after trauma a risk factor for ED?…”
Section: Introductionmentioning
confidence: 99%
“…The same researcher palpated nodules within the repair site in 93.7% of 352 patients with PF, who had undergone surgical treatment and monitored for 93.6 months without any physical examination evidence of Peyronie's plaque. 16 Similarly, in another study, no Peyronie's plaque could be found in 37 cases who were surgically treated for PF and followed for about 18 months. 17 On the other hand, in two separate controlled studies including 82 and 134 patients with PD, respectively, none of the cases had PF history.…”
Section: Discussionmentioning
confidence: 86%
“…In recent studies, development of the Peyronie's plaque in cases with PF treated surgically was assessed using only physical examination. [15][16][17] In this study, potential development of sequelas in tunica albuginea and intracavernosal septa of the cases treated surgically for PF within the last 20 years have been evaluated with physical examination, ultrasonography (US) and magnetic resonance imaging (MRI).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they reported the development of ED in 8 patients (80%) out of 10 who had not received surgical repair. 20 In another study, Ibrahiem et al 5 reported the rate of ED as 7.8% (11/155) after treatment in patients with penile fracture. They explained the causes of ED in those 11 patients as follows: 4 patients had incompetent veno-occlusive mechanism, 3 patients had penile artery insufficiency, and 4 patients had psychogenic trauma, as their color duplex penile indexes were normal.…”
Section: Discussionmentioning
confidence: 96%
“…In earlier studies, reports of conservative management have shown that nonsurgical management in penile fracture is unacceptable and complication rate was higher than with surgery. 20 Although the hospital stay for patients treated conservatively averaged 14 days, this period is usually limited in surgical groups to 1-2 days. 21 Our results show that a mean hospital stay of 2.1 days is consistent with the literature and supports recommendations for a surgical approach to penile fracture.…”
Section: Discussionmentioning
confidence: 99%